Sematech : saving the U.S. semiconductor industry - Browning, Larry D.; Shetler, Judy C. (College Station : Texas A & M University Press, 2000)
Annotation "In Sematech, Larry D. Browning and Judy C. Shetler trace the history of Sematech, a consortium formed by fourteen major American semiconductor manufacturers and the U.S. government. Sematech's founders were aware that consortia emphasizing cooperative research had been unsuccessful; Sematech planned a different approach. Its founding charter stated its goal: "To provide the U.S. semiconductor industry the capability for world leadership in manufacturing"--In other words, improve core manufacturing competence without making end products." "Browning and Shetler's history will inform and engage business historians, managers, public policy scholars, and others interested in the development and success of the U.S. computer chip industry and the application of its techniques to other fields of business."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Contents -- Preface -- Long-Established Relations Drive Cooperation -- The Black Book Sets the Structure -- Collaboration amidst Controversy -- Start-up Struggles -- Reaching Consensus on Standards -- Supplier Relations Lead toward Partnering -- Quality -- A New Mission -- Learning from the Sematech Experiment -- The Complexities of Sematech -- Chronology -- Sematech Centers of Excellence -- Intel's FourkStep Model for Constructive Confrontation -- Notes -- Bibliography -- Index
Includes bibliographical references (pages 243-259); references (p. 261-266) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: SEMATECH (Organization) -- History; SEMATECH (Organization); Semiconductor industry -- Government policy -- United States; Semi-conducteurs -- Industrie -- Politique gouvernementale -- États-Unis.; BUSINESS & ECONOMICS -- Infrastructure; BUSINESS & ECONOMICS -- Corporate & Business History; Semiconductor industry -- Government policy; United States; History